2016
DOI: 10.1177/2151458516672284
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Usage During Admission in Hip Fracture Patients—The Effect of the Continuous Femoral Nerve Block

Abstract: Introduction:The aim of this study was to investigate whether there was a difference in opioid usage during admission for hip fracture patients with continuous femoral nerve block (cFNB) when compared to patients nonfemoral nerve block (nFNB).Methods and Materials:Patients were identified from the local database on all hip fracture patients admitted to Bispebjerg University Hospital, Denmark. Four hundred fifty-six hip fracture patients were included during the period September 2008 to October 2010.Results:Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 14 publications
3
12
1
Order By: Relevance
“…One of the perceived benefits to the use of nerve block techniques is the opioid-sparing effect that they provide. Unlike Chaudet et al , 28 we found no difference in common opioid-related side effects (nausea and constipation); Helsø et al 30 found no morphine-sparing effect. The relatively low nausea rates in this study compared with others may explain some of this difference.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…One of the perceived benefits to the use of nerve block techniques is the opioid-sparing effect that they provide. Unlike Chaudet et al , 28 we found no difference in common opioid-related side effects (nausea and constipation); Helsø et al 30 found no morphine-sparing effect. The relatively low nausea rates in this study compared with others may explain some of this difference.…”
Section: Discussioncontrasting
confidence: 83%
“…Gille et al 29 used the same infusion regimen as this study and found no difference in pain relief between the catheter group and a systemic analgesia group over 3 days. A retrospective database study from Helsø et al 30 found no difference in morphine consumption during the first 5 days of admission between those given continuous femoral nerve blockade and those without.…”
Section: Discussionmentioning
confidence: 98%
“…Both FNB and FIB were able to substantially minimize opioid consumption in this part, and no significant differences were observed between them. As with previous studies, our findings are in line with those of others [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 94%
“…Better pain relief, shorter time for SA, and more stable mean artery pressure with FNB and FICB are well reflected in the satisfaction of the patient perioperatively. The present study is comparable to previous studies that showed that FNB or FICB was more effective in decreasing pain, shortening the time to perform SA, and increasing patient satisfaction [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 90%
“…Hemodynamic optimization has been advocated for the surgery of superaged patients with hip fracture in recent years. In addition, targeted nerve blocks provide a new approach to enhance recovery after surgery; they include obturator nerve and lateral femoral cutaneous nerve blocks, which will be beneficial for pain relief [26], and iliotibial membrane block, which will help reduce the incidence of postoperative delirium [27].…”
Section: Reviewmentioning
confidence: 99%